Retroperitoneal schwannoma mimicking a metastatic lymph node of renal clear cell carcinoma: a case report - Shaorong Pan; Pengyuan Wang; Zeyang Chen; Yucun Liu; Zhengfei Zhou (Frontiers in Neurology, 2024)
Schwannomas are usually benign tumors typically found in the head, neck, and extremities, with approximately 3% originating in the retroperitoneum. In this case, a young male presented with incidental masses in the left kidney and retroperitoneum. Abdominal pelvic enhanced computerized tomography (CT) revealed a tumor apparently originating from the left kidney, along with a retroperitoneal mass suspected to be a metastatic lymph node. Subsequently, a radical nephrectomy of the left kidney and retroperitoneal mass resection was performed. Pathological examination confirmed the left kidney mass as renal clear cell carcinoma and the retroperitoneal mass as schwannoma. The patient recovered uneventfully and was discharged from the hospital. A 6-month postoperative follow-up showed no evidence of recurrence. Preoperative diagnosis of schwannomas concurrent with other concurrent malignancies in rare sites, such as the retroperitoneum, is challenging due to their rare and non-specific radiological features. Although retroperitoneal schwannomas are rare, they should be considered in the differential diagnosis during CT examinations for renal cancer. Additionally, the advantages of a multidisciplinary team approach should be utilized in tumor management.